Enhancing Entrepreneurial Intentions through Self-Efficacy: A Study of Art Students in Hubei, China - Qin, Zhang (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2025)
Purpose: This study explores the influence of five variables—entrepreneurial education, self-efficacy, personal attitude, social norms, and perceived behavioral control on the entrepreneurial intentions of art students at a university in Hubei, China. The focus is particularly on identifying which factors significantly affect these intentions. Research design, data and methodology: Employing a mixed-method approach, the research collected data from 60 students using quantitative surveys and qualitative interviews. Multiple linear regression analysis was utilized to determine the impact of each variable on entrepreneurial intentions. All participants were involved in a 14-week strategic intervention program, with data from pre- and post-intervention analyzed through paired-sample t-tests. Results: The regression analysis confirmed that self-efficacy (H2) had a significant and positive impact on students’ entrepreneurial intentions, highlighting its pivotal role compared to the other variables tested. This research underscores the importance of enhancing self-efficacy to foster entrepreneurial intentions among students. Conclusions: Educational institutions can leverage these insights to design interventions that effectively cultivate an entrepreneurial mindset, especially focusing on boosting self-efficacy among students in creative fields.